SPRENGEL’S DEFORMITY - Durrani, Muhammad Younus Khan; Sohail, Abdul Malik Amir Hamza; Khan, Inamullah; Hashmi, Pervaiz (Journal of Ayub Medical College Abbottabad, 2018)
Various shoulder bone deformities have been identified in the pediatric age group, with the most common being undescended scapula. Sprengel’s deformity is dysplasia and malposition of the scapula, especially in the supraspinatus portion, mainly due to abnormal descent in the embryonic period. The clavicle is shorter and has a different contour. In some patients cervical spine deformities are also noted. This is a case of 3 years old girl presented to the clinic with difficulty in abducting right shoulder and sleeping with an internal rotation of the right arm. With physical examinations and radiological investigations sprengel’s deformity was diagnosed. Sprengel’s deformity is a male predominant disease which almost never occurs in isolation and is usually associated with deformities in the thoracic rib cage and the cervical and thoracic vertebrae. Our patient also had hyperpigmentation along the lines of Blaschko, which has never been previously reported with Sprengel’s deformity. Sprengel’s may have an association with cutaneous mosacism syndrome Keywords: Sprengel’s deformity; shoulder deformity; cutaneous mosacism syndrome